Strong relationoship between aerobic fitness and total distance covered in junior soccer players - Dujic, I.; Trajkovic, N.; Kristicevic, T. (Acta Kinesiologica, 2016)
Field and laboratory based physiological testing has become common among competitive field soccer players. However, how performance in such tests relates to performance during game playremains undetermined. Therefore, the purpose of this cross-sectional study was to examine the relationship between aerobic fitness and match performances among junior soccer players. Thirty seven junior soccer players were randomly selected using as stratification criteria age and playing role. Aerobic fitness was measured by laboratory and field tests. In addition, total distance covered during the match was determined. The total distance covered was associated with all variables of aerobic fitness. In addition, regression analysis showed that all tests for assessing aerobic fitness had significant impact on that criterion variable Total distance. Results showed that soccer players must have well physiological profile which allows them to achieve great sport results on important competitions.